Respiratory outcomes of adrenergic beta-antagonists in patients undergoing tracheal extubation: a systematic review and meta-analysis of randomized controlled trials - Lucas Cael Azevedo Ramos Bendaham; Altair Pereira de Melo Neto; Hilária Saugo Faria; André Richard da Silva Oliveira Filho; Carlos Henrique de Oliveira Ferreira; Marcela da Silva Kazitani Cunha; Victor Gonçalves Soares; Ocílio Ribeiro Gonçalves; Milene Vitória Sampaio Sobral; Mohamed Doma; Denis Maltz Grutcki; Fabrício Tavares Mendonça (Brazilian Journal of Anesthesiology)
Background: Tracheal extubation after general anesthesia may cause hemodynamic and respiratory complications, with no established strategies to prevent them. We conducted a meta-analysis to evaluate the safety and efficacy of beta-blockers in patients undergoing tracheal extubation. Methods: We searched the MEDLINE, EMBASE and CENTRAL databases for randomized controlled trials up to 2024 comparing beta-blockers to placebo in patients undergoing tracheal extubation. Primary outcome: cough intensity; secondary: bronchospasm, bucking, hypertension. Risk Ratios (RR) with 95% Confidence Intervals (95% CI) were computed. Leave-one-out sensitivity and meta-regression analyses were performed for outcomes with high heterogeneity. Results: We included 31 randomized studies, comprising 1,803 patients, of whom 965 received beta-blockers. The risk of moderate/severe cough (RR = 0.21; 95% CI 0.13 to 0.34; p < 0.001; I2 = 0%) and hypertension (RR = 0.28; 95% CI 0.13 to 0.58; p < 0.001; I2 = 45%) was significantly lower in the beta-blockers group compared with the placebo group. There were no statistically significant differences between groups in the risk of bronchospasm (RR = 0.58; 95% CI 0.17 to 1.94; p = 0.375; I2 = 0%) or bucking (RR = 0.47; 95% CI 0.20 to 1.13; p = 0.093; I2 = 72%). Sensitivity analysis identified Mendonça (2023) as the main heterogeneity source in bucking. Conclusion: Our study demonstrates that beta-blockers reduced moderate/severe cough and hypertension in patients undergoing tracheal extubation compared with placebo with no significant difference in the risk of bronchospasm and bucking. These findings suggest beta-blockers may be a valuable strategy for preventing peri-extubation hemodynamic instability and airway hyperresponsiveness. Prospero register: CRD42024542103.